A computed tomography-based preoperative risk scoring system to distinguish lymphoepithelioma-like gastric carcinoma from non-lymphoepithelioma-like gastric carcinoma - Li, Liming; Huang, Wenpeng; Hou, Ping; Li, Weiwei; Feng, Menyun; Liu, Yiyang; Gao, Jianbo (Frontiers in Oncology, 2022)
Abstract Purpose To develop a preoperative risk scoring model for distinguishing lymphoepithelioma-like gastric carcinoma (LELGC) from non-LELGC based on contrast-enhanced computed tomography (CT) images. Methods Clinicopathological features and CT findings of patients with LELGC and non-LELGC at our hospital between January 2016 and January 2021 were retrospectively analyzed and compared. A preoperative risk stratification model and a risk scoring system were developed using logistic regression. Results Twenty patients with LELGC and forty patients with non-LELGC were included. Epstein–Barr virus (EBV) infection and vascular invasion differed significantly between two groups (P<0.05). Significant differences were observed in the distribution of location, enhancement pattern, homogeneous enhancement, lymph node status and attenuations in the non-contrast, arterial, and venous phases (all P<0.05). Preoperative risk identification model included enhancement pattern, lymph node status and attenuations in venous phase. The area under the receiver operating characteristic curve, sensitivity, specificity and accuracy were 0.904, 87. 5%, 80.0% and 85.0%, respectively. The optimal cut-off score for distinguishing LELGC from non-LELGC was 3.5. Conclusion A preoperative risk identification model based on CT imaging data could be helpful for distinguishing LELGC from non-LELGC.